Supplements for yearling steers on bluestem pastures during the latter part of the grazing season, 1956, and a three-year summary, 1953-55-56. - Smith, E.F.; Cox, R.F.; Koch, B.A.; Walker, G.L. (Kansas Agricultural Experiment Station, 2011)
The nutritive value of bluestem pasture usually declines rapidly after midsummer. This is the third trial in this experiment in an attempt to find a method to economically increase the rate of gain after midsummer with small quantities of concentrate feed.
Keywords: Beef; Steers; Gain; Supplementation